Komunikasi Kriminal : AnalisisResepsi Untuk Melihat Pemaknaan Bagi Kepentingan Pembelaan - Achmad, Ardan (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2008)
The audience   has been   central  in mass  communication    research  from  the  very beginning.   Initially the audience  was perceived as an undifferentiated   mass,  as a passive   target  for persuasion   and  information,   or as market   of  consumers   of media  products.   Students  of media  effects  soon  came  to recognize  that  actual audiences   are made  up of real social groups  and are characterized  by networks of  interpersonal   relationship   through   which  effects  are  mediated  Audiences can also resist influence  in part because   they  have their own  varied reasons  for choosing     to   attend    to   the   media    message,    or   seeing    it   from   criminal communication     field,  for  the  sake  of  defences  interest   in  a  court  room,   an individual,  or group   of  individuals,  or  to  be  specifically, a defendant,   can give different   meanings   to  a preferred  meeninq  constructed   by  media,   in line  with his or  their  own  interest,  particularly  in  the  form  of  an  tdeological  resistance interpretation.